An empirical study on the determinants and optimal level of corporate cash holding from US firms - Cai, Shengfu (2016)
After the 2008 financial crises, people become aware of how important the role played by corporate cash holding in financial decision. In addition, in recent years, the cash holding for US firms are continuously increasing. Then it raises a question that is it good for firms to hold cash as much as possible? Numerous previous studies investigate the existence of optimal cash holding, but they got two opposite results. Some literatures support trade-off theory and think that there is an optimal level of cash holding for firms. On the other hand, some people agree the pecking order theory and hold the point that optimal level of cash holding does not exist. The purpose of this study is to test whether the optimal level of cash holding exist by examine 9686 US firms from 2004 to 2015. In this paper, the study is divided into several steps. Firstly, the determinants of cash holding will be determined. Secondly, mean reversion property of cash holding will be test. Thirdly, target adjustment model will be used in both trade-off theory and pecking order theory. Finally, the partial adjustment model will be examined. The results show that except tax, all other variables are consisted with previous researches. In addition, cash holding have the mean reversion property. Furthermore, regressions of target adjustment model present that trade-off theory have better explanation for cash holding than pecking order theory, therefore it support the view that firms exist optimal level of cash holding and firms with more cash tend to have slower adjustment speed. Finally, partial adjustment model also prove the existence of optimal cash holding.